Selected, Adopted and Implemented Social-Emotional Learning Program: the Kindness Curriculum for Kids - Uşakli, Hakan (Educational Challenges, 2021)
The aim of this manuscript is to introduce the program of social-emotional learning. Developed by the Centre for Healthy Minds (CHM) this program is called the Kindness Curriculum (CHM, 2017). Founded by the world renowned neuroscientist Dr. Richard J. Davidson, the Centre for Healthy Minds offers a kinder, wiser, more compassionate world. Methodology. Qualitative research method was used in this study. The methods of documentary research, observation and interview were also applied. The Kindness Curriculum was employed as a documentary study. The target audience and the object of observation were primary school children aged 6 to 7, the teachers were interviewed. Results. The mission of the centre is to cultivate kindness and relieve suffering through the scientific study of the mind. There are some social-emotional training programs, but the program developed by the centre is free. This program has been used by preschools and some researchers. The study involves the adaptation of the Kindness Curriculum to Turkish culture. The program contains twenty-four lessons in eight topics. These lessons include short stories, songs and entertaining games. The program can be conducted by one specialist both in preschool institutions and in primary classes. During the adaptation process, the program was translated into Turkish by two specialists and they controlled the entire translation process, which balanced the adaptation of the program by 80%. The benefits of the program for Turkish children have been studied by three psychologists. The program was used as a pilot research in the first grade of primary school. Conclusions. There are many positive results of the program application implemented by teachers. Schools are encouraged to add this program to their curriculum, and there is a need for more experimental research on the usefulness of the proposed program.